2021
DOI: 10.1108/rmj-12-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

A framework for digital preservation of Indigenous knowledge system (IKS) in repositories in South Africa

Abstract: Purpose The purpose of this study is to assess the digital preservation policies and plans for long-term digital preservation in selected repositories in South Africa, with a view to develop a digital preservation framework for the preservation of Indigenous knowledge system (IKS) in South Africa. Design/methodology/approach Through the multiple case study research design, data was obtained from eight respondents in four Indigenous Knowledge Systems Documentation Centers (IKSDCs) in institutions that are par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…These online engagements range from restricted online databases to stand-alone databases with community-only access to public webpages of varying standards (Scott, 2004). The globalization of Africa’s IK can only happen if there is a deliberate approach to capturing, documenting, storing and providing access to such knowledge on the Web (Balogun and Kalusopa, 2021). One way of ensuring this is for African countries to set up national IK resource centres (Chisenga, 2002; Plockey, 2014), which revealed that lack of human resource, finance, infrastructure, internet connectivity and copyright, among other things, poses a great challenge in the digitization of IK.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These online engagements range from restricted online databases to stand-alone databases with community-only access to public webpages of varying standards (Scott, 2004). The globalization of Africa’s IK can only happen if there is a deliberate approach to capturing, documenting, storing and providing access to such knowledge on the Web (Balogun and Kalusopa, 2021). One way of ensuring this is for African countries to set up national IK resource centres (Chisenga, 2002; Plockey, 2014), which revealed that lack of human resource, finance, infrastructure, internet connectivity and copyright, among other things, poses a great challenge in the digitization of IK.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Balogun and Kalusopa (2021, p. 79) note that there are few studies on the preservation of digital resources in Southern Africa. This study’s researchers are unaware of a more comprehensive literature review that assesses the state of digital preservation practices within the national departments of the South African public sector, which suggests strategies for improved digital preservation to achieve good governance, effective public service delivery and transparency.…”
Section: Problem Statementmentioning
confidence: 99%
“…In their recent assessment of policies and plans for long-term preservation in South African repositories, Balogun and Kalusopa (2021) developed a framework to ensure the authenticity, integrity and trustworthiness of South African resources. Data was collected from eight respondents in four Indigenous Knowledge Systems (IKS) Documentation Centers in institutions that are part of the National Recordal Systems initiative across four provinces using a multiple case study research design.…”
Section: Establishing Digital Preservation Policies Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many have linked it to the restrictions of the new normal. However, despite either lack of care or expertise, the truth remains that there is a general belief that preservation of knowledge in academic institutions is at a challenging state in general and in Global South Countries in particular (Balogun, 2021). This paper has identified the building and management of digital collections in academic institutions as a way out of this critical situation and sustainable development goals.…”
Section: Introductionmentioning
confidence: 99%